Dimensi Keterkaitan Influencer Marketing, EWOM (Electronic Word Of Mouth), dan Online Customer Rating pada Keputusan Pembelian Produk Fashion Muslim pada E-commerce Shopee (Studi Kasus pada Mahasiswa FEB Universitas Islam Malang) - Artanti, Leni; Nurhidayah, Nurhidayah; Sholehuddin, Sulton (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The purpose of this study is to analyze the influence of influencer marketing, EWOM (Electronic Word Of Mouth), and online customer rating on the purchase decision of Muslim fashion products on Shopee e-commerce. This study utilizes explanatory research methods through a quantitative approach. The data analysis technique used multiple linear regression analysis. Sampling through non-probability sampling with purposive sampling method. The number of respondents as many as 70 people who are Shopee e-commerce users and have purchased Muslim fashion products at Shopee.  The results show that influencer marketing, EWOM (Electronic Word Of Mouth), and online customer rating simultaneously influence purchasing decisions and each independent variable have a partial effect on purchasing decisions. Keywords: Influencer Marketing, Electronic Word Of Mouth, Online Customer Rating, Purchase Decision